The impact of short-term debt on accruals-based earnings management: Evidence from Vietnam - Trinh Quoc Trung; Nguyen Thanh Liem; Cao Thi Mien Thuy (Cogent Economics & Finance, 2020)
This study seeks to examine the relationship between short-term debt maturity and accruals-based earnings management using a sample of listed firms in Vietnam from 2010-2017. The extant literature remains under-explored on the impact of short-term debt on accruals-based earnings management at low and high levels of short-term debt. We further dissect the impact of the interaction between the growth opportunities and short debt maturity on accruals-based earnings management. Our findings provide evidence suggesting that short-term debt maturity is likely to exert a desirable impact in lowering earnings management at low levels of short-term debt, while at high levels it tends to increase earnings manipulation, demonstrating a U-shaped relationship. Furthermore, we show that growth opportunities moderate the impact of short debt maturity on earnings management. Specifically, the U-shaped pattern between short-term debt and earnings management is pronounced for firms with low growth opportunities, while for high-growth counterparts that pattern weakens.
Keywords: 330; short-debt maturity; earnings management; growth opportunities; non-linearimpact